Acúmulo de forragem e fotossíntese foliar de faixas etárias de perfilhos do capim-marandu sob duas condições de adubação - Carvalho, Angélica Nunes de (2017)
The tillers are the basic units of growth of the forage plant. The age groups of the tillers, as well as the fertilization, influence the forage production of the forage canopy. The objective of this work was to understand the development and contribution of young, mature and old tillers for the accumulation of canopy of Urochloa brizantha cv. Marandu (Marandu grass) during the year and in response to fertilization. The design was completely randomized, with four replications. Two fertilization strategies (low fertilizer and high fertilizer), three age groups of tillers (young, mature and old) and four seasons of the year (winter, early spring, late spring and summer) were evaluated. In general, the growth characteristics were higher in the high fertilizer condition and in the seasons with higher rainfall and temperature. Nitrogen and phosphate fertilizations in the marandu grass increase the population density of tiller and promote greater growth of the forage canopy. The percentage of young tillers is higher in late spring and summer than in autumn and winter. The young tiller has higher leaf and stalk growth than the old tiller, but this contributes the highest growth rate of the canopy. The young tiller presents a greater contribution to the leaf accumulation rate of the canopy of the marandu grass. Key-